A Primer on the oxDNA Model of DNA: When to Use it, How to Simulate it and How to Interpret the Results - Sengar, A.; Ouldridge, T. E.; Henrich, O.; Rovigatti, L.; Šulc, P. (Frontiers in Molecular Biosciences, 2021)
The oxDNA model of DNA has been applied widely to systems in biology, biophysics and nanotechnology. It is currently available via two independent open source packages. Here we present a set of clearly-documented exemplar simulations that simultaneously provide both an introduction to simulating the model, and a review of the model's fundamental properties. We outline how simulation results can be interpreted in terms of -- and feed into our understanding of -- less detailed models that operate at larger length scales, and provide guidance on whether simulating a system with oxDNA is worthwhile.